2007
DOI: 10.1097/wad.0b013e318032cf29
|View full text |Cite
|
Sign up to set email alerts
|

Memantine Treatment of Cognitive Symptoms in Mild to Moderate Alzheimer Disease: Secondary Analyses From a Placebo-controlled Randomized Trial

Abstract: Memantine, an N-methyl-D-aspartate receptor antagonist, is approved in the United States and Europe for the treatment of moderate to severe Alzheimer disease (AD) and has also been investigated in patients with mild to moderate AD. To characterize the specific cognitive benefits of memantine in patients with mild to moderate AD, a post hoc analysis was conducted of a 24-week randomized, double-blind, placebo-controlled, clinical trial comparing memantine (10 mg twice daily) to placebo. Cognition was assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 13 publications
1
21
0
2
Order By: Relevance
“…However, memantine is under investigation as a potential treatment for other diseases as well, including traumatic and hypoxic brain injuries [23,24]. In AD, memantine monotherapy or combined with cholinesterase inhibitors improved attention, memory, and language functions [19,25]. Based on the current findings, increased cerebral glucose metabolism in the frontal lobe, including the dorsolateral prefrontal cortex, and in the parietal lobe, including the precuneus, the angular gyrus, and the inferior parietal lobule, may be associated with the previously reported cognitive enhancing effects of memantine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, memantine is under investigation as a potential treatment for other diseases as well, including traumatic and hypoxic brain injuries [23,24]. In AD, memantine monotherapy or combined with cholinesterase inhibitors improved attention, memory, and language functions [19,25]. Based on the current findings, increased cerebral glucose metabolism in the frontal lobe, including the dorsolateral prefrontal cortex, and in the parietal lobe, including the precuneus, the angular gyrus, and the inferior parietal lobule, may be associated with the previously reported cognitive enhancing effects of memantine.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, positive effects of memantine treatment for neurodegenerative diseases [19], stroke [20], neuropathic pain [21], and schizophrenia [22] have been reported. However, memantine is under investigation as a potential treatment for other diseases as well, including traumatic and hypoxic brain injuries [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, an earlier clinical trial (MD-10) demonstrated that memantine treatment produced significant improvements in cognition, global status, and behavior compared with placebo [6]. Afterwards, a post hoc analysis of this trial found that, compared to the control group, the memantine group exhibited significantly smaller declines on the spoken language, comprehension, word finding, orientation, and recall of test instructions items of the ADAS-cog and demonstrated significant advantages on the language and memory subscales, but not the praxis subscale, of the ADAS-cog at week 24 [19]. Our study and the MD-10 study included a higher percentage of moderate AD patients (73.7% in our study, 67.4% in the MD-10 study) than the 99679 study (51.6%).…”
Section: Discussionmentioning
confidence: 99%
“…The CIBIC-Plus and the MMSE were assessed at baseline and at week 24. For the secondary analysis, the 12 items of the ADAS-cog were aggregated into 4 subscales according to a previously published factor analysis [19]; the subscales included memory (word recall, naming objects and fingers, orientation, word recognition, and remembering test instructions), language (commands, spoken language, word finding, and comprehension), praxis (construction and ideational praxis), and attention. Each item of the NPI was compared between the two treatment groups.…”
Section: Methodsmentioning
confidence: 99%
“…Neue Ergebnisse sprechen auch für eine Wirksamkeit der Cholinesterasehemmer im Stadium der schweren AD [4] und von Memantin bei leichter AD [23].…”
Section: Potenzielle Indikationenunclassified